The Comparison of Bearing Capacity Calculation Obtained based on SPT-N from Seismic Survey against Strength Parameters (c’ and φ) value from Soil Drilling - Kamarudin, Mohamad Aiman Syafiq (IRC, 2016)
Soil investigation is a method of obtaining data for a particular area regarding the properties of subsoil which includes fieldworks and laboratory tests. Nowadays, conventional techniques are mostly used for soil investigation but there are a few disadvantages of using it have been discovered. The disadvantages of using conventional techniques are costly, time consuming, destructive and limited of equipment mobilization. The scope of study for this research is to determine the bearing capacity calculation obtained based on two different methods which are SPT- N from seismic survey and strength parameters (c’ and φ) from soil drilling.